Noise reduction algorithm in hearing aids: influence on speech recognition in noisy environment (Research, Society and Development, 2020)
Purpose: To verify the influence of the noise reduction algorithm on speech recognition of adults and elderly users of hearing aids. Method: Cross-sectional study conducted with 18 years or older individuals with sensorineural hearing loss, referred for hearing aids fitting. It was used the List of Sentences in Portuguese test in an acoustically treated cabin under two conditions: noise reduction algorithm on and off. Results: There was an improvement in the Signal-to-Noise ratio in the condition of noise reduction on compared to noise reduction off (p = 0.043). Regarding the Speech Recognition in Noise Index, no statistically significant differences were observed. Two variables were defined: ΔSNR and ΔSRNI. ΔSNR is the difference between the Signal-to-Noise ratio with noise reduction off and on, while ΔSRNI is the difference between Speech Recognition in Noise Index with noise reduction on and off. An increase in ΔSNR is related to a worsening of ΔSRNI. Conclusion: The Signal-to-Noise ratio improved with the use of the noise reduction. However, this was not verified for the SRNI. In addition, an inverse relationship between ΔSNR and ΔSRNI was observed, implying that an improvement in Signal-to-Noise ratio may compromise the speech recognition in noise.